Cooperative Trading House Dalam Pemberdayaan UMKM Jawa Timur Perspektif Hifdzul Aql - Ana Toni Roby Candra Yudha; Izzuddin M. Afif; Mochammad Andre Agustianto (Universitas Airlangga, 2022)
This study aims to identify and explain the role of the Cooperative Trading House (CTH) in an effort to empower Small and Micro Enterprises (SMEs) in East Java which will be reviewed on the hifdzul aql perspective in maqashid sharia. The method used in this study is a descriptive qualitative method with a case study approach. This research will explain and describe phenomena or events that occur in the research subject or CTH. Cooperative Trading House is an institution formed by the East Java Cooperatives and SMEs Service. This institution aims to accelerate the marketing process so that SMEs so that they can be more empowered. The results of the study prove that CTH has many programs, services, and consultations to help SMEs related to marketing. With these results, it is relevant to give appropriate advice, namely the need for empowerment efforts that are more inclined to increase the knowledge and abilities of SMEs, so that it is related to hifdzul aql. This research also bring any comtribution to related research on empowerment especially in maqashid syariah perspective.